Методична компетентність вчителя історії та правознавства як складова професійної компетентності - Прокопчук, Вікторія (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті подаються погляди зарубіжних та вітчизняних учених та окремі офіційні документи, де визначено ряд освітніх понять, зокрема: «компетентність», «професійна компетентність», «методична компетентність вчителя»; запропоновано власне бачення професійної та методичної компетентності вчителя загалом та вчителя історії та правознавства зокрема;. методична компетентність розглядається як складова професійної; подано зміст методичної компетентності вчителя історії та правознавства. Examples of a number of concept interpretations such as "competence", "professional competence", "teacher professional competence" and "methodical competence of the teacher" are regarded in the article. We distinguish the following constituent elements of professional competence of teachers (teacher of history and law): subject (history, law), psychological, educational, methodical, informational and communicative, professionally important personal qualities (creativity, organization, responsibility, speaking skills, kindness, empathy, etc.) and internal demand to constant self-education and professional development and growth. All these professional competences stay in constant communication and are interdependent. Nature of professional competence of the teacher of history and law is analyzed in detail. Methodological competence is a part of the professional competence of teachers and provides a set of knowledge and skills of subject teachers needed for teaching students the basics of certain sciences (history, law). The place of methodical competence of the teacher is very important. It completes the formation of professional competence of teacher in terms of higher educational institution and brings students directly to teaching practice. Our vision of methodical competence of the teacher of history and law is as following: the teacher should have a set of knowledge and skills to implement a number of methodological problems: the formation of historical and juridical knowledge of pupils; methods of education of students at the lessons of history and law, and during extracurricular activity; developing abilities, skills and competencies of students in the process of study of history and law; understanding the nature and ability to establish interdisciplinary and intersubject connections in the process of education (interdisciplinary integration, knowledge and skills of students); knowledge of teaching methods and methodology of their usage; the lessons of history, law (requirements for lessons, preparation stages, classification types, structure, preparation of a compendium) review and assessment of students’ achievements. In professional activity of a teacher methodical competence is the base for the educational process to study history and law.
Keywords: компетентність; професійна компетентність; професійна компетентність вчителя; методична компетентність вчителя історії та правознавства